Evaluation of Microscopic Changes in Fallopian Tubes of BRCA Mutation Carriers by Morphometric Analysis of Histologic Slides: A Preliminary Pilot Study. (September 2018) - Amit, Amnon; Sabo, Edmond; Zohar, Yaniv; Trugman, Einat; Pranovich, Irena; Reiss, Ari; Matanes, Emad; Klorin, Geula
Abstract : Mutations in BRCA genes increase the risk of ovarian cancer, yet no method for early diagnosis is available. Some serous ovarian tumors are hypothesized to stem from cells of the fallopian tube fimbria. Using a novel method of computerized morphometry of the fimbrial epithelium, this study aimed to detect morphologic differences in noncancerous fimbriae between BRCA mutation carriers and noncarriers, and between healthy and serous ovarian cancer patients. Twenty-four fimbriae from healthy women (13 BRCA+, 11 BRCA−) and 21 fimbriae from women with serous ovarian cancer (10 BRCA+, 11 BRCA−), all reported as "normal" by hematoxylin and eosin examination, were subjected to computerized histomorphometric analysis. A Fast Fourier Transformation was applied to images of fimbrial epithelium and the Fast Fourier Transformation 2-dimensional frequency maps were subsequently quantified for nuclear orientation and planar distribution by a cooccurrence matrix analysis. Additional analysis of nuclear contour was applied to the fimbriae of the healthy women. Among the healthy women, significant differences were found in morphometric characteristics between the BRCA mutation carriers and noncarriers. Among the women with ovarian cancer, no significant differences were found between BRCA mutation carriers and noncarriers. Between healthy women and those with ovarian cancer, significant differences were detected, regardless of BRCA mutational status. A novel method, which combined Fast Fourier Transformation with cooccurrence matrix analysis, demonstrated differences in morphometric characteristics in the fimbriae between healthy and ovarian cancer patients, and between BRCA mutation carriers and noncarriers. The clinical significance of these observations should be investigated.